Adásvételi szerződések a 16. század első felében Besztercebánya szabad királyi bányavárosban - Kuzma, Dóra (Közép-Európai Közlemények, 2017)
This paper seeks to outline briefly how property purchase contracts developed in the first half of the 16th century in Besztercebánya (Banska Bystrica), a mining town in Lower Hungary. Based on the 1542 sixtieth tax census, Oszkár Paulinyi concluded that the city had 2600–2900 inhabitants with 171 houses, resulting an average 15–17 residents per home value. The town center (Ring) had a symbolic value with 32–36 houses. Living here meant much more than owning a house, it meant social prestige. These houses were sold on a much higher price than the others situated in streets leading from of the Ring or situated outside of the city wall; although their equipments and other accessories, excluding water pipes are not known. In Besztercebányaa there was a significant real estate commerce in the 16th century. We can draw the following conclusion: the city council interfered with private matters, but with ensuring fair contracts. The number of house sales were high but the city council did a great job the securing the commerce and avoiding fraud contracts. The Ring remained in the hands of the rich German elite, even if the houses changed their owners. The system of commerce with significant value was working and was stabile without major hitches.